Effects of Clove and Fermented Ginger on Blood Glucose, Leptin, Insulin and Insulin Receptor Levels in High Fat Diet- Induced Type 2 Diabetic Rabbits (Nigerian Journal of Physiological Sciences, 2021)
Summary: The aimed of this research is to evaluate the effects of clove and fermented ginger supplements on blood glucose, serum insulin, insulin receptor and Leptin levels of high fat diet-induced type 2 diabetes mellitus in rabbits. Clove and ginger are spices with records of medicinal value over decades. Thirty males rabbits weighing, 1–1.5kg were used for the research. Type 2 diabetes was induced by feeding the animals with a high fat diet for a period of eight weeks. Blood glucose levels were determined after the induction period and rabbits having 140 mg/dL and above were selected for the study. The animals were grouped into six groups with five (n=5) rabbits in each group: Group 1 (Normoglycemic control group.) received normal feed and distilled water ad libitum for six weeks; Group 2 (Diabetic negative control group.) received normal feed and distilled water ad libitum for six weeks; Groups 3 (Diabetic positive control.) received cholestran 0.26g/kg and normal feed for a period of six weeks; Group 4 and 5 (diabetic rabbits) were fed on 12.5%, clove and 12.5% fermented ginger respectively for a period of six weeks; while Group 6 were co-fed on 12.5% clove and 12.5% fermented ginger for a period of six weeks. Fasting blood glucose levels were determined at weekly interval during the treatment period. At the end of the experiment, the rabbits were euthanized by cervical dislocation and blood samples were collected for the determination of insulin, insulin receptor and leptin levels. A significantly (P